PEMBAGIAN WARIS ANAK ANGKAT BERDASARKAN HUKUM WARIS ADAT AMBON - Winny Amanda Darwin; Ning Adiasih (Fakultas Hukum Universitas Trisakti, 2021)
Customary law is a law that is recognized and developed in Indonesian society. An adopted child is a child legally adopted from another person, through adoption, the status of the adopted child changes from not being a biological child to becoming an adopted child who is legally recognized or has the same position as a biological child. The problem in this material is how the position of adopted children in Ambon customary inheritance law. The type of research conducted is normative which is descriptive in nature supported by secondary data, then analyzed qualitatively, by drawing conclusions carried out by the deductive method. As stipulated in the customary inheritance law in Ambon Landraad Amboina Decree No.14/1920 that in inheriting the position of adopted children the same as biological children as long as their appointment is before a notary or court and with the approval of the Head of Saniri Negri and heir children or biological children of parents he adopts, in other words, it is not enough just to get the approval of the head of the State Saniri, without the approval of the heirs, that adopted children cannot inherit the right to inherit along with their biological children.